O Internato Rural e a formação do profissional médico para o Programade Saúde da Família - Emanuel Vitor Guimaraes (2004)
The availability of physicians with an adequate profile is very important for the improvement of Family Health strategy. The objective of this research was to comprehend how a discipline of medical graduation of Minas Gerais Medical Sciences School, the Rural Internship, in which the students develop their activities integrated with the Family Health Program (PSF), may influence the formation of the students, especially in the preparation to be acting in the PSF team after their graduation. A qualitative methodology was used, and the data collection was carried out through semi-structured interviews with the students in the end of the period of learning of the discipline. The analysis of the results showed an adequate involvement of the students with the activities of the PSF teams and the development of knowledge, attitudes and skills in common with the attributions defined to the physician in the PSF. The researchconcludes that the Rural Internship has a favorable influence upon the formation of the students and, within its limits, contributes to make them more prepared to perform in the PSF, makes considerations on how to improve the discipline and the medical graduation in the School, and about the importance of the advance of both in the integration with the PSF and with the Unified Health System (SUS).